ТHEORETICAL ASPECTS OF ENTERPRISE LABOUR POTENTIAL EVALUATION - Andriichuk , Yu.A.; Hladun , S.O. (The actual problems of regional economy development, 2018)
The article has considered the modern conditions of domestic enterprises functioning. The relevance of an enterprise labour potential evaluation is analyzed. The concepts of value and evaluation of enterprise labour potential have been separated. The core objective of labour potential evaluation has been determined. The tasks of enterprise labour potential evaluation have been defined concretely. In our days, the urgency of enterprise labour potential evaluation is growing, as it is a rational basis for its management in order to increase the efficiency of enterprise management system at all. The further researches should consist in studying and systematization of indicators in order to develop the unified methodology of enterprise labour potential evaluation.